Cell Adhesion Molecules in Neuroblastoma: Complex Roles, Therapeutic Potential - Heinly, Briana E.; Grant, Christa N. (Frontiers in Oncology, 2022)
Neuroblastoma, a biologically heterogeneous tumor derived from neural crest cells, accounts for approximately 15% of childhood deaths from cancer. Recently, scientific literature has explored the role of cell adhesion molecules (CAMs) in cancer metastasis through cell detachment, migration, and invasion. Through a review of the current literature, it is evident that expression of different CAMs on neuroblastoma tumors is associated with favorable or unfavorable clinical prognosis. In patients diagnosed with neuroblastoma, treatment strategies include chemotherapy, surgery, radiotherapy, stem cell transplant, and more recently, immunotherapy and other targeted therapies. Long term survival remains poor despite multimodality treatment, especially for children with high-risk neuroblastoma, making it more necessary to explore innovative targeted therapies. CAMs have immense potential as therapeutic targets, but there is a need for growth and scientific exploration before CAM therapies become clinically useful.